The effect of added wire mesh on the thermal efficiency of the flat plate solar water heater collector - Sabaa Theeyzen; Basim Freegah (Results in Engineering)
The current study looks into the effects of using wire mesh to expand the flat plate solar collector (FPSC) on the system's thermal efficiency under transient heat-flux without changing its dimensions and its placement to minimise the shadows cast on the collector while utilising passive methods to circulate the working fluid. Thus, the traditional model was investigated numerically (using ANSYS fluent) and experimentally to establish the accuracy of simulation results. Then, the three models, A, B, and C, were tested numerically. In model A, the mesh is used to cover the riser pipe. In model B, the mesh covers the collector plate; in model C, the mesh is placed on both the riser pipe and the plate. The wire mesh placement in all three models improved the thermal efficiency of the FPSC. In addition, model C proved to be paramount to all models under study, classical models A and B, by having a higher thermal efficiency of 41.4 %, 14 %, and 31.2 %, respectively.